Kepatuhan Perawatan pada Pasien Diabetes Mellitus Tipe 2 - I Made Mertha; I Made Widastra; I Gusti Ayu Ketut Purnamawati (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2014)
This study aimed to identity treatment adherence in patients with Diabetes Mellitus Type 2in Interna Policlinic at Negara General Hospital. This was a quantitative descriftive study with crossectional subject-approach model. This study use the non probability sampling with 30 sample. Sampling technicque with consecutive sampling technique that use questionnaires treatment adherence. The results obtained is 14 respondents (46,7%) treatment adherence and 4 respondents (13,3%) not treatment adherence.